Analisis Pengadaan Obat di Rumah Sakit - Alma Marinda; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
A hospital is an individual health care institution that provides inpatient, outpatient, and emergency services. The statement is based on the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016 concerning Pharmaceutical Service Standards in Hospitals. Drug processing management is an important part of drug management in hospitals, and if one process is not appropriate, it will hinder or affect the drug management system. The hospital does not have standards in recording and planning budgets for the procurement of drugs and other facilities, late delivery of expeditions or late disbursement of BPJS funds must be reconsidered seeing that many communities and hospitals use funds from the BPJS system. Collaborating with other hospitals, pharmacies and with the Health Office can help to meet the availability of drugs.